Concerns and experiences of nursing students during their internship in public health: example of Şanlıurfa - Emma Danella (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The objective of the study is to describe the concerns and experiences of nursing students who will complete an internship in public health for the first time. Method: This is a descriptive study conducted among 27 nurses who completed a public health internship at the Harran University School of Health. Data were collected using a semi-structured interview form. Results: All male students went on home visits with their girlfriends. They said they couldn't communicate directly during home visits and the internship was not very effective in this state. Conclusion: Male students faced resistance in public health practices, so it was determined that they were not beneficial to both society and themselves, learning diminished, and change was slow.